Classical dynamics a contemporary approach - Jose, Jorge V. (Jorge Valenzuela) 1949-; Saletan, Eugene J. (Eugene Jerome) (Cambridge University Press, 1998)
"Recent advances in the study of dynamical systems have revolutionized the way that classical mechanics is taught and understood. Classical Dynamics: A Contemporary Approach is a new and comprehensive textbook that provides a complete description of this fundamental branch of physics." "It will be an ideal textbook for graduate students of physics, applied mathematics, theoretical chemistry, and engineering, and will also serve as a useful reference for researchers in these fields"--Jacket.